1985
DOI: 10.1002/art.1780280903
|View full text |Cite
|
Sign up to set email alerts
|

A rheumatoid arthritis b cell subset expresses a phenotype similar to that in chronic lymphocytic leukemia

Abstract: An abnormal subpopulation of B cells expressing the T1 antigen, which is normally restricted to T cells, was demonstrated in the peripheral blood of 16 patients with rheumatoid arthritis. This T1+ B cell population accounted for a mean of 19.6% (upper limit 48%) of the circulating B cells and did not correlate with clinical disease activity, rheumatoid factor, or drug treatment. The highest percentage of T1+ B cells found in the blood of 8 patients with connective tissue diseases, including systemic lupus eryt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
64
1

Year Published

1989
1989
2006
2006

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 218 publications
(71 citation statements)
references
References 26 publications
(23 reference statements)
6
64
1
Order By: Relevance
“…CD5 + B cells, a special subtype of B cells, showed faint discontinuous HRP deposits and various depositions of gold particles on the cell surface. This finding agrees with the immunofluorescence findings described above 9 . In addition, three types of CD5 + B cells were identified based on the cellular morphology (organelles, chromatin patterns, microvilli, the N/C ratio, and the NCI) 20 and the labeling patterns of HRP deposits and/or gold particles 13,15 .…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…CD5 + B cells, a special subtype of B cells, showed faint discontinuous HRP deposits and various depositions of gold particles on the cell surface. This finding agrees with the immunofluorescence findings described above 9 . In addition, three types of CD5 + B cells were identified based on the cellular morphology (organelles, chromatin patterns, microvilli, the N/C ratio, and the NCI) 20 and the labeling patterns of HRP deposits and/or gold particles 13,15 .…”
Section: Discussionsupporting
confidence: 93%
“…Immunofluorescence analysis has shown that CD5 + B cells are morphologically similar to conventional B lymphocytes 6,9 , whereas the fluorescence intensity of CD5 + B cells labeled with anti-CD5 antibody is weaker than that observed for labeled T cells, suggesting a lower epitope density in the B cell subpopulation. Although conventional MayGrünwald-Giemsa staining has shown that these cells have basophilic cytoplasm with indented nuclei, and rarely have nucleoli 6 , no immunoelectron microscopic studies of CD5 + B cells have been reported.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…These cells are characterized by the production of low-affinity immunoglobulin M (IgM) with RF activity, arise early in ontogeny and are considered to represent the bridge linking the innate and acquired immune responses [24]. The production of circulating autoantibodies coupled with their increased frequency in rheumatoid arthritis and Sjögren's syndrome has implicated them in the development of autoimmune diseases [25,26]. In addition, CD5 + B cells are also increased in Epstein-Barr virus and human immunodeficiency virus (HIV) infections associated with autoimmune manifestations as well as in patients with essential mixed cryoglobulinaemia [27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…Many of the antibodies have several specificities and some are autoreactive (12)(13)(14). CD5+ B cells are elevated in several autoimmune disorders as well as genetically autoimmune mice (13,(15)(16)(17)(18). They have also been implicated in formation of a primordial idiotype-anti-idiotype network (12)(13)(14).…”
mentioning
confidence: 99%